Answer:
[tex]\frac{K.E_t}{K.E_r} = 1[/tex]
Explanation:
The translational kinetic energy of the hoop is given as:
[tex]K.E_t = \frac{1}{2} mv^2[/tex] ---------------------- equation (1)
where,
[tex]K.E_t[/tex] = translational kinetic energy
m = mass of hoop
v = linear speed of hoop
The rotational kinetic energy of the hoop is given as:
[tex]K.E_r = \frac{1}{2} I\omega^2[/tex]
where,
[tex]K.E_r[/tex] = rotational kinetic energy of the hoop
I = Moment of Inertia of the hoop = mr²
r = radius of the hoop
ω = angular speed of hoop = [tex]\frac{v}{r}[/tex]
Therefore,
[tex]K.E_r = \frac{1}{2} (mr^2)(\frac{v}{r} )^2\\\\K.E_r = \frac{1}{2} mv^2[/tex]------------------- equation (2)
dividing equation (1) and equation (2), we get:
[tex]\frac{K.E_t}{K.E_r} = \frac{\frac{1}{2}mv^2 }{\frac{1}{2}mv^2 }\\\\\frac{K.E_t}{K.E_r} = 1[/tex]